Interaksi Dosis dan Intensitas Urea Daun pada Serapan N serta Hasil Padi Rawa - Palupi, Dora; Susianti, Helda; Mahmudin, Mahmudin; Analisa, Widya; Shofiyah Anjani, Anisa (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Rice (Oryza sativa L.) is a staple food crop that serves as the primary source of carbohydrates for the majority of the Indonesian population. Swamp lands have distinctive characteristics due to prolonged water saturation, often leading to nitrogen losses through denitrification, volatilization, and leaching processes. This study aims to determine the extent to which variations in the dosage and intensity of foliar urea fertilizer application can affect nitrogen distribution in plant tissues (roots, stems, and leaves) and how it influences the grain weight per plot. The study used a completely randomized block design (CRBD) with 3 replications. The first factor was the concentration of urea solution, consisting of 4 levels: 3% (D1), 6% (D2), 9% (D3), and 12% (D4). The second factor was the intensity of urea fertilizer application, consisting of 3 levels: once (I1) (2 weeks after planting), twice (I2) (2 and 4 weeks after planting), and three times (I3) (2, 4, and 6 weeks after planting). The application of urea fertilizer on leaves with variations in dose and intensity significantly affects nitrogen uptake and rice grain yield. Increasing the dose up to 12% and applying it up to three times enhances nitrogen uptake and grain yield. A dose of 9% with three applications produces the highest nitrogen uptake, while a 12% dose results in the highest grain weight without a significant difference between one and three applications